2018
DOI: 10.1002/jum.14554
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of a Low‐Lying Placenta and Placenta Previa Diagnosed at the Midtrimester Anatomy Scan

Abstract: A low-lying placenta or placenta previa diagnosed at the midtrimester anatomy survey resolves in most patients. Resolution is near universal in patients with an initial distance from the internal os of 10 mm or greater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 19 publications
1
41
0
Order By: Relevance
“…One study found that vaginal ultrasound helped diagnose low-lying placenta or placenta previa in nearly 1 in 10 women. [ 5 ] MRI has good soft tissue contrast and clearly shows the placenta position and the depth of myometrial invasion. MRI and computed tomography can be valuable for a placenta previa diagnosis when ultrasound results are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that vaginal ultrasound helped diagnose low-lying placenta or placenta previa in nearly 1 in 10 women. [ 5 ] MRI has good soft tissue contrast and clearly shows the placenta position and the depth of myometrial invasion. MRI and computed tomography can be valuable for a placenta previa diagnosis when ultrasound results are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Resolution was noted in 99.5% in women with an IOD of 10-20 mm, 95.4% with an IOD of 0.1-10mm and 72.3% with a placenta previa. 7 The higher percentage of normal location of second trimester low-lying placentas compared to placenta previa might be due to trophotropism. This is a process of atrophy of the thin placental margins due to a poor vascular supply in the lower uterine segment, whereas other placenta regions continue to grow and migrate towards sites with a higher vascular density in the fundal region of the uterus.…”
Section: Discussionmentioning
confidence: 99%
“…13 The higher rate of persistence of placentas on the posterior side compared to the anterior side found in our cohort was also described by others. 7,13,14 It might be associated with dynamic placentation, in which the anterior uterine wall expands more than the posterior wall. Since the uterus grows gradually by elongation and hypertrophy during pregnancy, the lower uterine segment will lengthen.…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…11 However; there is no consensus about the exact distance, which can give the obstetricians a high sensitivity rate of diagnosis. 12 Additionally, the maternal characteristics may be also having a role in prediction of PP.…”
Section: Introductionmentioning
confidence: 99%